The impact of health anxiety on life satisfaction among male university students in sports sciences - Osman Pepe; İbrahim Dalbudak; Özdemir Atar; Berat Koçyiğit; Mustafa Deniz Dindar (Journal of Men's Health)
Background: In recent decades, there has been a notable decline in healthy lifestyle activity levels and a rise in unhealthy habits, particularly among university students. These trends are concerning, as behaviors developed during university years can negatively affect long-term life satisfaction. The aim of this study is to examine the effect of health anxiety on life satisfaction levels of male university students enrolled in sports sciences. Methods: The study population consisted of male university students studying sports sciences, with a sample of 421 students selected by a simple random sampling method. Data were collected using a researcher-designed personal information form, and the health anxiety and life satisfaction scales in the literature. Statistical analysis were conducted using SPSS 22.0 (IBM SPSS Statistics, Chicago, IL, USA). Pearson correlation analysis was applied to determine the relationships between variables and simple regression analysis was employed to assess the effect of health anxiety on participants’ life satisfaction. Results: The findings revealed a weak level of negative correlation between health anxiety and life satisfaction among male university students in sports sciences. Furthermore, health anxiety was found to significantly impact life satisfaction. Conclusions: This study highlights the need for targeted interventions to promote physical activity among university youth. Addressing the physical activity in university years may contribute to healthier lifestyles, and reduced health anxiety and improved life satisfaction in the long term.